Some Outcomes of an Employment-Oriented Post-Secondary Training Program for Educably Mentally Handicapped Adults - Fahy, P.; McLean, A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The Alberta Vocational Centre (AVC) Transitional Vocational (T-V) Program, in Edmonton, began in 1982. The program currently employs six instructors to provide a postsecondary employment-oriented program for mildly mentally disabled adults. The yearlong program is offered in two sessions and has an approximate enrollment of 30 incoming students and 12-18 outgoing students in each session. Students are assessed at the Goodwill Rehabilitation Society and then assigned either to a regular class or a differentiated class incorporating more experiential learning and group instruction. An evaluation of the program was conducted in January-April 1987 by a telephone survey of 1982-1985 graduates of the program. Additional information was obtained and comparisons made from an earlier study. Some of the conclusions drawn were the following: (1) the T-V gender ratios are approximately equal; (2) T-V graduates are younger than the AVC's regular students; (3) T-V graduates of both genders averaged 71 on the Wechsler Adult Intelligence Scale-Revised (WAIS-R); (4) T-V graduates were about as likely to be employed as regular AVC graduates (56 to 63 percent); (5) changing jobs is three times more common among T-V graduates than among graduates of other AVC programs; (6) T-V graduates earn less than AVC graduates, and females earn less than males; (7) WAIS-R scores are not related to employability, although age may be related and gender probably is related; (8) T-V graduates work at some time after graduation, males more so than females; (9) most T-V graduates like their jobs (men less than women) and are satisfied with their income (women less than men); (10) most T-V graduates want to work now and/or expect to be working in the future; and (11) male T-V graduates are initially, and remain, more dependent on family for residence and employment than females. (KC)
ERIC Note: Based on a presentation to the American Association on Mental Deficiency, Region IV Conference, "Working toward Self-Sufficiency" (Edmonton, Alberta, Canada, September 16, 1987).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Education Work Relationship; Employment Programs; Foreign Countries; Job Skills; Job Training; Mild Mental Retardation; Outcomes of Education; Postsecondary Education; Program Effectiveness; Program Implementation; Technical Education; Vocational Education; Work Experience Programs; Alberta Vocational Centre (Edmonton); Speeches/Meeting Papers; Reports, Descriptive